The Fit Family Challenge: A County-wide, Web-based Physical Activity Initiative. Issue 3 (23rd March 2020) - McWilliams, Stephanie R.; Bulger, Sean; Keath, Adam; Elliott, Eloise
Abstract : The Fit Family Challenge, a web-based healthy lifestyle program, was developed to motivate families to participate in more physical activity by tracking their behaviors and by providing them with educational materials and community events to attend with their families. This article is an account of the steps taken and the efforts needed to make a county-wide family physical activity initiative such as the Fit Family Challenge successful.